Intuitive eating was associated with anxiety, depression, pregnancy weight and blood glucose in women with gestational diabetes mellitus: a prospective longitudinal study - Gao, Xiao xia; Zheng, Qing xiang; Chen, Xiao qian; Jiang, Xiu min; Liao, Yan ping; Pan, Yu qing; Zou, Jing jing; Liu, Gaoqian (Frontiers in Nutrition, 2024)
Background: Outside of pregnancy, intuitive eating (IE) is associated with lower body weight, blood glucose, and higher positive mood. However, little was known about the relationship between IE and anxiety-depression in the GDM population. Thus, this study aimed to investigate the association of IE with anxiety and depression, pregnancy weight and pregnancy blood glucose in the first and second GDM visit. Methods: Data from 310 pregnant women with GDM from the Fujian Maternal and Child Health Hospital Trial (Approval Number: 2020Y9133) were analysed. IE was assessed using the Intuitive Eating Scale-2 subscales of Eating for Physiological Reasons rather than Emotional Reasons (EPR), Relying on Hunger and Satiety Cues (RHSC) and Body-Food Choice Consistency (B-FCC). Observations included weight, body mass index (BMI), fasting plasma glucose (FPG) and 2-hour postprandial blood glucose; the Hospital Anxiety and Depression Scale (HADS) was used to assess the level of anxiety and depression in pregnant women with GDM. Linear regression analysis was used to assess the correlation between IE and anxiety, depression, pregnancy blood glucose and weight. Results: The cross-sectional analysis showed that the EPR eating behavior was negatively correlated with anxiety and depression, and the B-FCC eating behavior was negatively correlated with depression at both the first and second GDM visit; in addition, the B-FCC eating behavior was associated with lower BMI in the third trimester (all P < 0.05). In longitudinal analyses, the EPR eating behavior in the first visit for GDM predicted lower levels of anxiety and depression in the second GDM visit, whereas the RHSC eating behavior in the first visit for GDM was associated with lower FPG in the second GDM visit (all P < 0.01). Conclusions: These results suggest that practicing intuitive eating may be beneficial and that higher intuitive eating adherence can lead to lower levels of anxiety and depression and more ideal gestational weight and blood glucose values.